1997
DOI: 10.1111/j.1532-5415.1997.tb00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Medicine and Screening in Older Adults

Abstract: The goal of preventive medicine in older people should be not only reduction of premature morbidity and mortality but preservation of function and quality of life. Attempts to prevent diseases of old age should start in youth; the older the patient, the less likely the possibility or value of primary and secondary prevention, and the greater the stress must be on tertiary prevention. Age 85 is proposed as a general cutoff range beyond which conventional screening tests are unlikely to be of continued benefit; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 142 publications
0
60
0
5
Order By: Relevance
“…1 Despite recommendations for preventive services by organizations such as the U.S. Preventive Services Task Force (USPSTF), elders' receipt of services is suboptimal. For example, one study found that although 91% of female Medicare beneficiaries aged 65 years and older receive at least one preventive service, only 10% receive all that are appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite recommendations for preventive services by organizations such as the U.S. Preventive Services Task Force (USPSTF), elders' receipt of services is suboptimal. For example, one study found that although 91% of female Medicare beneficiaries aged 65 years and older receive at least one preventive service, only 10% receive all that are appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…For items related to health conditions, questions about the frequency and type of screening were based on recommendations by the Canadian Task Force on Preventive Health Care and the US Preventive Services Task Force and other relevant literature. [8][9][10] For breast cancer, respondents were asked whether they had received a mammogram or had had their breasts examined for "lumps" in the 2 years before the survey. For heart disease and stroke, they were asked about yearly blood pressure measurements and cholesterol screening.…”
Section: Methodsmentioning
confidence: 99%
“…Some illnesses may shape clinical priorities or treatment patterns and alter interest in new conditions, or they may lessen the likelihood of routine disease screening. For example, patients with Alzheimer's disease are less likely to receive routine screening tests such as mammograms (15). Comorbidity may alter disease presentation and outcomes because of combined bodily stresses.…”
Section: Impact Of More Advanced Disease and Comorbiditymentioning
confidence: 99%